2010
DOI: 10.3386/w16396
|View full text |Cite
|
Sign up to set email alerts
|

Inequality at Work: The Effect of Peer Salaries on Job Satisfaction

Abstract: We use a simple theoretical framework and a randomized manipulation of access to information on peers' wages to provide new evidence on the effects of relative pay on individual job satisfaction and job search intentions. A randomly chosen subset of employees of the University of California (UC) was informed about a new website listing the pay of University employees. All employees were then surveyed about their job satisfaction and job search intentions. Our information treatment doubles the fraction of emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
172
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(188 citation statements)
references
References 24 publications
8
172
2
6
Order By: Relevance
“…6 As Clark et al (2008) have pointed out, the bulk of the literature has defined relative income as income earned by people with similar individual characteristics-such as age, education, or civil status-and confined to a common social sphere-e.g., same company, same neighborhood, or doing the same kind of job. These comparison income measures are generally constructed in a number of ways, which include: (i) predicting individual wages from Mincer equations Sloane and Williams 2000;Lévy-Garboua and Montmarquette 2004;Senik 2004); (ii) calculating cell averages according to specific individual characteristics within-sample or (iii) out-of-sample from external data McBride 2001;Luttmer 2005;Clark et al 2009a;Card et al 2010); and (iv) computing average wages of workers' colleagues (Rizzo and Zeckhauser 2003;Brown et al 2008;Clark et al 2009b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…6 As Clark et al (2008) have pointed out, the bulk of the literature has defined relative income as income earned by people with similar individual characteristics-such as age, education, or civil status-and confined to a common social sphere-e.g., same company, same neighborhood, or doing the same kind of job. These comparison income measures are generally constructed in a number of ways, which include: (i) predicting individual wages from Mincer equations Sloane and Williams 2000;Lévy-Garboua and Montmarquette 2004;Senik 2004); (ii) calculating cell averages according to specific individual characteristics within-sample or (iii) out-of-sample from external data McBride 2001;Luttmer 2005;Clark et al 2009a;Card et al 2010); and (iv) computing average wages of workers' colleagues (Rizzo and Zeckhauser 2003;Brown et al 2008;Clark et al 2009b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While individuals may directly derive utility from a high social standing, the imitation of the spending of the rich could also be instrumental to other goals such as success in the competition for marriage partners or professional success. In addition, empirical evidence from the happiness literature suggests that comparisons appear to be mostly upward: Having low relative standing negatively affects satisfaction, but individuals do not derive much satisfaction from a high relative position (Ferrer-i Carbonell, 2005;Senik, 2009;Card et al, 2012).…”
Section: A Model Of "Keeping Up With the 'Rich' Joneses"mentioning
confidence: 99%
“…Furthermore, PA may induce higher levels of pay dispersion within a company, which potentially reduces employee satisfaction when employees, for instance, dislike inequity. A number of studies have shown that relative pay comparisons among employees, especially the individual rank in income distributions, have a negative impact on job and pay satisfaction and negatively affect effort provision (Brown et al, 2008;Clark et al, 2010;Card et al, 2012;Ockenfels et al (forthcoming)). Another drawback of formal PA might be a crowding out of intrinsic motivation due to the pronounced focus on extrinsic incentives (Deci et al, 1999;Frey & Jegen, 2001).…”
Section: Theory Performance Appraisals and Job Satisfactionmentioning
confidence: 99%